History, identity and meaning : Cape Town's Coon Carnival in the 1960s and 1970s - Baxter, Lisa Mary (Department of Historical Studies, 2016)
Little has been written about the Coon Carnival since its inception in the late nineteenth century. This thesis helps remedy the general neglect of popular, "Coloured", working class history during the apartheid years. attempts to situate Cape Town's New Year Carnival within the international debate surrounding popular festival and identity. Following a broadly historical line of inquiry, this thesis straddles different disciplines, borrowing from a range of interpretative fields to assess the form and significance of the event during the 1960s and 1970s, a critical period in the Carnival's history. During these years, District Six - the event's symbolic and spiritual home - was declared for "White" residence only under the Group Areas Act. Coloured residents were forcibly removed from this central city suburb to disparate areas on the Cape Flats - the townships surrounding the metropolis. A year later, in 1967, the carnival parade was effectively banned from the city centre's streets; banished to remote and enclosed stadium venues. Thus, in a relatively short space of time the Carnival came under sustained attack. Due to the relative dearth of critical engagement with, or historical commentary on, the Carnival, this thesis relies heavily on oral sources and journalistic, visual and tourist oriented representations. Focussing particularly on the oral testimonies of twenty-four people involved in the event, it explores the notion of continuity and change in the Carnival during this period, through a thorough interrogation of the narratives.